Policy for the Development and Education Management of Entikong Border Area on Political Economic Perspective - M. Uhaib; Muhammad Yuliansyah; Elyta Elyta; Murakhman Sayuti Enggok; Isdairi Isdairi; Kasypul Anwar (UIN Sunan Gunung Djati, 2022)
Entikong is a border area with a vibrant economy developing border areas between countries in terms of economy and education as a supporting factor for Entikong as a growth center in Sanggau Regency. Problems like this impact the economic development and social dynamics of the Entikong community. This study aims at Development Policy and Education Management in the Entikong Border Area from a Political Economy Perspective as a solution to regional development. Qualitative research methods, with literature studies, complement the results of qualitative research. The research results on Development Policy and Education Management in the Entikong Border Area from a Political Economy Perspective, namely First, Entikong Border Area Development Policy from a Political Economy Perspective, strengthening the regional potential and utilizing village funds can encourage the development of the Entikong border area. The possibility of Sanggau Regency in the Entikong border area includes agriculture and plantations such as oil palm and pepper, which are only regional commodities and can be optimally optimized for the development of the Entikong border area and through export and import economic activities through the Entikong border, then also through village funds provided by the government can be used to improve infrastructure and public facilities in the village as a support for economic activities for development. Second, the Education Management Policy in the Entikong Border Area from a Political Economy Perspective by improving the level of education in the Entikong border area, which can become capital and future investment for the progress and development of the Indonesian state.